Challenges. Students book 1 - Harris, Michael and Mower, David (Harlow Pearson Education Limited, 2009)
Challenges is a new four level course for teenagers which gives them everything they need to be successful in learning English. Written by the authors of the global bestseller.
Keywords: Teaching English